The game, and approach to the reduction of the obesity (Review) (Revista científica Olimpia, 2020)
The research carried out refers a characterization about obesity, taking into account definitions, its classification and the role of game as part of physical exercise with the aim of decreasing the obesity in adults. The purpose of the research is to relate the game as a way to contribute to the reduction of obesity, taking into account that through it an appropriate time is used in physical exercise and recreation, which together are added as ways of rehabilitation through energy expenditure and raising social welfare.
Keywords: obesity; game; physical exercise; health